MOTIVASI DAN PERSEPSI MASYARAKAT PULAU ENGGANO TERHADAP PENDIDIKAN - Abdul Rahman Singkam; Syaiful Rochman; Fitra Youpika (JURNAL ENGGANO)
This research aims to analyse the impact of motivation and perception of the society on the quality of education in Enggano island: one of the 111 outermost islands in Indonesia. Despite lacking of supporting facilities is still a main problem of education in Enggano, non-physics (motivation and perception) data are expected to provide alternative solution. Data in this research was collected by using semi-open questionnares to all qualified respondents. 579 quetionnaires in total were fulfilled by six categories of respondents: the students of elementary-, junior- and senior high school, teachers, parents, and the village leaders. Our results show that the motivation of students in Enggano is sufficiently high: 78 out of 100, while the perception of parents and teachers to education is on the medium level: 65 out of 100. The village leaders have graded the quality of education in Enggano on 5.6+0.17 out of 10. Besides of the medium level on perception, a low integrity among the teachers also contributed to the backwardness of eduaction in Enggano.MOTIVATION AND PERCEPTION OF ENGGANO ISLAND COMMUNITIES ON EDUCATION. This research aims to analyse the impact of motivation and perception of the society on the quality of education in Enggano island: one of the 111 outermost islands in Indonesia. Despite lacking of supporting facilities is still a main problem of education in Enggano, non-physics (motivation and perception) data are expected to provide alternative solution. Data in this research was collected by using semi-open questionnares to all qualified respondents. 579 quetionnaires in total were fulfilled by six categories of respondents: the students of elementary-, junior- and senior high school, teachers, parents, and the village leaders. Our results show that the motivation of students in Enggano is sufficiently high: 78 out of 100, while the perception of parents and teachers to education is on the medium level: 65 out of 100. The village leaders have graded the quality of education in Enggano on 5.6+0.17 out of 10. Besides of the medium level on perception, a low integrity among the teachers also contributed to the backwardness of eduaction in Enggano.